P53 regulates a mitotic transcription program and determines ploidy in normal mouse liver12. Issue 5 (15th February 2013) - Kurinna, Svitlana; Stratton, Sabrina A.; Coban, Zeynep; Schumacher, Jill M.; Grompe, Markus; Duncan, Andrew W.; Barton, Michelle Craig
Abstract: Functions of p53 during mitosis reportedly include prevention of polyploidy and transmission of aberrant chromosomes. However, whether p53 plays these roles during genomic surveillance in vivo and, if so, whether this is done via direct or indirect means remain unknown. The ability of normal, mature hepatocytes to respond to stimuli, reenter the cell cycle, and regenerate liver mass offers an ideal setting to assess mitosis in vivo . In quiescent liver, normally high ploidy levels in adult mice increased with loss of p53. Following partial hepatectomy, p53 −/− hepatocytes exhibited early entry into the cell cycle and prolonged proliferation with an increased number of polyploid mitoses. Ploidy levels increased during regeneration of both wild‐type (WT) and p53 −/− hepatocytes, but only WT hepatocytes were able to dynamically resolve ploidy levels and return to normal by the end of regeneration. We identified multiple cell cycle and mitotic regulators, including Foxm1, Aurka, Lats2, Plk2, and Plk4, as directly regulated by chromatin interactions of p53 in vivo . Over a time course of regeneration, direct and indirect regulation of expression by p53 is mediated in a gene‐specific manner. Conclusion : Our results show that p53 plays a role in mitotic fidelity and ploidy resolution in hepatocytes of normal and regenerative liver. (HEPATOLOGY 2013)